Высоковольтный импульсный генератор для электроразрядных технологий - Канаев Г. Г. Геннадий Григорьевич; Кухта В. Л. Владимир Романович; Лопатин В. В. Владимир Васильевич; Нашилевский А. В. Александр Владимирович; Ремнев Г. Е. Геннадий Ефимович; Уемура Кенсуке
опубл. 27.10.10